Efek Ekstrak Etanol Akar Pasak Bumi (Eurycoma Longifolia, Jack) terhadap Ekspresi HRAS pada Organ Hati Tikus Galur Sprague Dawley pada Pemberian Doxorubicin - Noval Noval; Raihana Raihana (Jurnal Surya Medika (JSM), 2019)
Doxorubicin chemotherapy agents cause serious side effects in normal cells, especially in the liver and heart caused by free radicals. RAS is an important component of the signal transduction pathway that controls cell proliferation, differentiation and survival. The pasak bumi root (Eurycoma longifolia, Jack) has been reported to have acted as an antioxidant and hepatoprotector. This study aims to determine the effect of giving ethanol extract of pasak bumi root on HRAS expression in healthy mice given doxorubicin. This research was conducted by dividing the test animals into 7 groups, namely doxorubicin control group 4.67 mg / kgBB, group II control ethanol extract of pasak bumi roots 200 mg / kgBB, group III, IV and V were the treatment groups given doxorubicin 4.67 mg / kgBW with ethanol extract of the pasak bumi root, each 50 mg / kgBB; 100 mg / kgBB; 200 mg / kgBW, group VI solvent control and group VII healthy control. The study was continued by painting using an immunohistochemical method to see the expression of HRAS in each experimental group. Data analysis was performed by calculating per cent expressions, then proceed with statistical tests using SPSS. The results of statistical tests showed that there were significant differences between the doxorubicin control group (18.56 ± 1.85) and the treatment of group 5 (10.43 ± 1.71) and there were no significant differences between the doxorubicin control group (18.56 ± 1, 85) with group 3 treatment (17.80 ± 4.23) and group 4 treatment (16.70 ± 1.97). From the results of the study concluded that the ethanol extract of pasak bumi roots at a dose of 200 mg / KgBB can reduce the expression of HRAS in the administration of doxorubicin